Effect of active vs. passive end-range determination on shoulder axial rotation in thrower athletes - Ribeiro, A.; Pascoal, G. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The effect of active or passive end-range determination on shoulder axial rotation is unclear on overhead-throwing athletes. Twenty-two healthy males were equally divided into athletes and non-athletes groups and their throwing arm was tested during internal and external arm rotation and on active and passive end-range determination conditions. The humeral and scapular 3D position were recorded at the shoulder rotational endrange and compared across groups using two-way repeated-measures ANOVA. No differences were found between groups for all humeral and scapular variables. The active internal Thoracohumeral (TH) and Glenohumeral (GH) arches were significantly (p=0.00) higher than internal passive TH and GH. At the end-range of external rotation athletes showed a scapula less in protraction (p=0.027) and less in scapular posterior tilt (p=0.00). External passive TH and GH were significantly higher than external active TH and GH.